2021
DOI: 10.3389/fmicb.2021.719548
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the ClpXP Protease Leads to Decreased Resistance to Cell-Envelope Targeting Antimicrobials in Bacillus anthracis Sterne

Abstract: The ClpX ATPase is critical for resistance to cell envelope targeting antibiotics in Bacillus anthracis, however, it is unclear whether this is due to its function as an independent chaperone or as part of the ClpXP protease. In this study, we demonstrate that antibiotic resistance is due to formation of the ClpXP protease through construction of a ClpX complementation plasmid that is unable to interact with ClpP. Additionally, we genetically disrupted both clpP genes, clpP1 and clpP2, found in B. anthracis St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 49 publications
(104 reference statements)
1
9
0
Order By: Relevance
“…ClpX is part of the ClpXP two-component protease in E. coli that is involved in cell division through FtsZ degradation ( Camberg et al 2011 ) and therefore associated with resistance to antibiotics that target the cell wall ( Bæk et al 2014 ), while Lon is an ATP-dependent protease associated with a wide range of cellular activities ( Luo et al 2008 ), including regulating transcript levels of marA and their target genes acrR , acrA , and tolC ( Nicoloff and Andersson 2013 ; Bhaskarla et al 2016 ). Lon has been shown in vitro to modify drug-resistance levels when there is a loss of function ( Matange 2020 ; Zou et al 2021 ). Both proteins, ClpX and Lon, have been associated with increased resistance ( Bæk et al 2014 ; Liu et al 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…ClpX is part of the ClpXP two-component protease in E. coli that is involved in cell division through FtsZ degradation ( Camberg et al 2011 ) and therefore associated with resistance to antibiotics that target the cell wall ( Bæk et al 2014 ), while Lon is an ATP-dependent protease associated with a wide range of cellular activities ( Luo et al 2008 ), including regulating transcript levels of marA and their target genes acrR , acrA , and tolC ( Nicoloff and Andersson 2013 ; Bhaskarla et al 2016 ). Lon has been shown in vitro to modify drug-resistance levels when there is a loss of function ( Matange 2020 ; Zou et al 2021 ). Both proteins, ClpX and Lon, have been associated with increased resistance ( Bæk et al 2014 ; Liu et al 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, these DEPs may directly or indirectly be regulated by ClpX protein . As a molecular chaperone, ClpX requires the recognition and binding of substrates to participate in protease-mediated protein degradation. ,, Here, we performed a streptavidin–biotin affinity pull-down assay coupled with label-free proteome quantitation to identify the ClpX-binding proteins. To further gain a comprehensive understanding of ClpX’s cellular function and regulatory network, we compared the ClpX-binding proteins in this study with previously identified ClpX-regulated proteins by quantitative proteomics .…”
Section: Resultsmentioning
confidence: 99%
“…Cyanobacterial peptidases have three different ClpP homologues (ClpP1, ClpP2, and ClpP3) and a ClpP-like protein known as ClpR that lacks the characteristic catalytic structure of Ser-type peptidases. , The activity of Clp systems in cyanobacteria relies on the AAA+ ATPase, either ClpC or ClpX . One of the crucial components of Clp systems in cyanobacteria is ClpXP, which consists of a heterotetradecameric ClpP1P2 core and a ClpX homohexameric ring . The ClpX homohexameric ring binds to a short unstructured peptide in a protein substrate, unfolds any stable tertiary structure, and then translocates the denatured polypeptide into the heterotetradecameric ClpP peptidase for degradation (Figure A) .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was shown that they also participate in growth under heat stress conditions, as in B. subtilis, and that they are required for the formation of the septum and the maintenance of cell shape [82,83]. The participation of ClpC in sporulation was also demonstrated in the enteropathogenic Bacillus thuringiensis (B. thuringiensis), which, like B. anthracis, has two isoforms of ClpP, ClpP1 and ClpP2, which have been related to the regulation of different types of stress [84,85]. As mentioned above, in B. subtilis, SpoIIAB is regulated by ClpCP, so a similar regulation was suggested in B. anthracis that would explain the decrease in sporulation, since in clpC mutants there is a loss of envelope of the spore [80,82].…”
Section: Role Of Clp In Sporulationmentioning
confidence: 99%
“…clpX mutant strains are rapidly eliminated in vitro by the antimicrobial peptides cathelicidin, α-defensin, and lysozyme [81]. It has also been suggested that ClpX participates in maintaining resistance to antimicrobial peptides LL-37 and nisine, and to the antibiotic penicillin and doptamicine [84]. Additionally, Listeria monocytogenes, a Gram-positive intracellular pathogen, possesses two ClpP isoforms, ClpP2 and ClpP1P2 (Figure 1).…”
Section: Role Of Clp In Survival and Virulencementioning
confidence: 99%